Analisis Kinerja Sistem Shopee: Optimalisasi Database Dalam Meningkatkan Pengalaman Pengguna - Nabila Keysha Mutmainah; Nayla Humaimah; Imam Fitrahwan; Nurbaiti (CV. ITTC INDONESIA, 2025)
This research aims to analyze the role of database optimization in improving system performance on the Shopee e-commerce platform, as well as its impact on user experience. Effective database management, including the use of indexes and caching techniques, is believed to speed up product searches, increase transaction speed, and support the system in handling spikes in user traffic. The research method used is a qualitative approach with a case study of active Shopee users. Data collection techniques were conducted through participatory observation and content analysis, which were then analyzed using thematic analysis. The results showed that database optimization plays an important role in improving Shopee's operational efficiency, such as speeding up the search and transaction processes, which contributes to increased user satisfaction. Nonetheless, some areas such as the speed of transactions using bank transfers and the relevance of product search results still require improvement. This research contributes both practically and theoretically in the development of technical strategies to improve user experience on e-commerce platforms.